Monitoring atmospheric pollution, gases and aerosols "online" in Sierra Nevada (October 2022 - September 2023) - Sonia Castillo; Diego Patrón; Lucas Alados-Arboledas (PANGAEA, 2024)
This dataset presents hourly raw data on gaseous atmospheric pollutants as sulphur dioxide (SO2), nitrogen oxides (NO/NO2/NOx), carbon monoxide (CO), ozone (O3), methane (CH4) and non-methane hydrocarbons (NMHC); and atmospheric particulate matter (PM10) at different locations in the Sierra Nevada National Park (southeastern Iberian Peninsula, Granada, Spain) during the period October 2022 - September 2023. The dataset is derived from two different measurements platforms, one fixed and one mobile. The fixed platform is sited at the Mojón del Trigo Observatory, a high-altitude remote station located in the north side of Sierra Nevada mountain range (SNS, 37.09° N, 3.38° W, 2605 m asl). This station is one of the main facilities of AGORA (Andalusian Global ObseRvatory of the Atmosphere). The mobile measurement platform is a mobile atmospheric observation unit (UMOVIL), that was moving through rural locations with different characteristics, on the south side of Sierra Nevada (ORG, 36.90° N, 3.42° W, 453 m asl; PAM, 36.94° N, 3.36° W, 1134 m asl; CAP, 36.96° N - 3.36° W, 1451 m asl). The dataset was recorded by gaseous and particulate matter analysers. The NO/NO2/NOx analyser (Thermo Scientific, model 42i in UMOVIL and 42i-TL in SNS) is based on the principle of chemiluminescence; the SO2 analyser (Thermo Scientific, model 43i in UMOVIL and 43i-TLE in SNS) is based on the principle of pulsed fluorescence; the CO analyser (Thermo Scientific, model 48i at both measurement platforms) is based on the measurement principle of non-dispersive infrared spectrometry (NDIR); the O3 analyser (Thermo Scientific, model 49i at both measurement platforms) is based on the principle of ultraviolet photometry; the PM10 analyser (Thermo Scientific, model TEOM 1405 at both measurement sites) is based on the gravimetric method for a direct determination of mass particles; and the hydrocarbons analyser (Synspec, model GC955-114 at both measurement platforms) is based on the principle of gas chromatography. The dataset presents hourly mean concentration of each species in micrograms per cubic meter.